2000
DOI: 10.1177/095624780001200207
|View full text |Cite
|
Sign up to set email alerts
|

Partnerships in urban environmental management: an approach to solving environmental problems in Nakuru, Kenya

Abstract: This paper considers the potentials and limitations of partnerships between municipal authorities and local and external groups in addressing environmental problems, and illustrates this with an account of the experience in the city of Nakuru in developing such partnerships. It describes the serious inadequacies in the provision for water, sanitation and solid waste management in Nakuru, and then describes the Localizing Agenda 21 Programme that was developed in the city, supported by a variety of national and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…Previous studies indicate that sanitation challenges in urban Africa are largely driven by poor disposal of human excreta and solid waste (e.g., Mwangi, 2000;Ouayoro, 2000;Simie, 2000;Thomas et al, 1999). Whilst Thomas et al's (1999) findings indicated that about 40% of urban residents in Accra (Ghana) used pit latrines and 19.5% used bucket latrines, Mwangi (2000) also found that 89% of urban residents in low income high density areas of Nakuru (Kenya) used pit latrines.…”
Section: High Incidence Of Vulnerability and Insecurity In Urban Africamentioning
confidence: 98%
“…Previous studies indicate that sanitation challenges in urban Africa are largely driven by poor disposal of human excreta and solid waste (e.g., Mwangi, 2000;Ouayoro, 2000;Simie, 2000;Thomas et al, 1999). Whilst Thomas et al's (1999) findings indicated that about 40% of urban residents in Accra (Ghana) used pit latrines and 19.5% used bucket latrines, Mwangi (2000) also found that 89% of urban residents in low income high density areas of Nakuru (Kenya) used pit latrines.…”
Section: High Incidence Of Vulnerability and Insecurity In Urban Africamentioning
confidence: 98%
“…Expansion of human settlements and cultivation, deforestation, land fragmentation and intensification of land use, pollution and hunting in the catchment of the lake have since restricted the wildlife mostly to within the national park, established in 1961. Nakuru town had expanded to cover some 124 km 2 by 1998, while its population grew from 14,000 people in 1948 to over 324,000 people by 2000 at a rate of 5-10% per annum (Mwangi 2000;Thampy 2002;Odada et al 2004).…”
Section: Introductionmentioning
confidence: 94%
“…In 1994, the government de-gazetted over 200 km 2 of the Eastern Mau Forest on the western divide of the catchment of the basin, a major national watershed, and the source of important streams feeding Lake Nakuru. Thereafter more than 300 km 2 of natural and plantation forests was cleared of trees for settlements, grazing and cultivation (Mwangi 2000;Thampy 2002;Odada et al 2004;Raini 2009b). These land use changes have reduced LNNP to an island surrounded by the rapidly expanding Nakuru town, settlements, cultivation and fences.…”
Section: Introductionmentioning
confidence: 97%
“…About 40% of the residents of Accra use pit latrines, 19.5% use bucket latrines, whilst 15.4% of the residents of Port Elizabeth use bucket latrines (Benneh et al, 1993;Thomas et al, 1999). In Nakuru, Kenya, 89% of the urban households use pit latrines in the low income high density areas of the city (Mwangi, 2000). It is estimated that 71% of the urban population in Senegal use pit latrines (Department of Forecasts and Statistics, 1993).…”
Section: Growing Waste Pollutionmentioning
confidence: 99%
“…This involves consultation with the people affected by environmental problems, and requires that people participate in the provision and maintenance of facilities. Participation can help build long-term capacity and enhance the ability of local people in managing and negotiating development projects (Mwangi, 2000).…”
Section: Slum Upgradingmentioning
confidence: 99%